Case report: A patient with Delayed Sleep-Wake Phase Disorder and Optic Nerve Hypoplasia treated with tasimelteon: a case study - Smieszek, Sandra P.; Kaden, Alyssa R.; Johnson, Caroline E.; Brzezynski, Jennifer L.; Xiao, Changfu; Polymeropoulos, Christos M.; Birznieks, Gunther; Emsellem, Helene A.; Polymeropoulos, Mihael H. (Frontiers in Neuroscience, 2023)
We present a case of an adult female diagnosed with Delayed Sleep-Wake Phase Disorder (DSWPD) and Optic Nerve Hypoplasia (ONH), with a confirmed delayed Dim Light Melatonin Onset (DLMO), who reports the inability to fall asleep at their desired bedtime and obtain adequate sleep nightly, despite the ability to have a full night's sleep when not required to be up at a specific time for societal requirements. The participant was enrolled in an 11-month Open-Label Extension (OLE) following the randomized portion of a clinical study and was successfully treated with tasimelteon. DSWPD symptoms were resolved, and their previously delayed sleep-wake cycle was advanced.